ترميم الضياعات المادية للأنسجة الرخوة في الساق باستخدام السدائل العضلية (التوأمية والنعلية) والسدائل الجلدية السفاقية(الربلية) - ملحم, فراس; يوسف, صفوان; جواد, عبد الحميد (Latakia University Journal -Medical Sciences Series, 2018)
مدخل إلى البحث: تعتبر الضياعات المادية في الساق من أهم التحديات التي تواجه جراحي الترميم بسبب قلة الأنسجة الرخوة المغطية للوجه الأمامي للساق ونقص التروية الدموية في الثلث البعيد منها، ويعتبر الترميم بالسدائل العضلية والجلدية السفاقية من أهم خيارات الترميم، قمنا في دراستنا بتقويم استخدام هذه السدائل حيث لا توجد دراسة محلية لذلك حتى الآن. هدف البحث: تقويم طرق ترميم الضياعات المادية للأنسجة الرخوة في الساق باستخدام السدائل العضلية والجلدية السفاقية ومقارنتها بالدراسات العالمية. طرائق البحث ومواده: قمنا بإجراء دراسة استرجاعية لمرضى الضياعات المادية في الساق والذين أجري لهم ترميم بالسديلتين العضليتين التوأمية والنعلية والسديلة الجلدية السفاقية المعكوسة (الربلية) بين عامي2015و2017 في مشفيي الأسد وتشرين الجامعيين في اللاذقية، من حيث سبب الضياع، وقت الترميم، السديلة المستخدمة وعيوشيتها ونجاحها، وكذلك الوظيفة الحركية والاضطرابات الحسية التالية، ورضا المرضى من الناحية الجمالية. النتائج والمناقشة: تضمنت عينة البحث 25 مريضا، تراوحت أعمارهم(13_55) سنة بمتوسط 42سنة، بلغ عدد الذكور23 والإناث2، وكان السبب الأكثر شيوعا ه والإصابات الحربية بنسبة60%، قمنا باستخدام السديلة النعلية للترميم في 6حالات(24%)، والتوأمية في 5 حالات(20%)، والتوأمية مع النعيلىة في حالة واحدة (4%) والربلية المعكوسة في 13حالة(52%)، وكانت العيوشية كاملة في 19حالة، وجزئية في5 حالات وحدث تنخر تام في حالة واحدة. الخلاصة: إن علاج الضياعات المادية بالسدائل الموضعية (الربلية، النعلية والتوأمية) يمكن من الحصول على نتائج مرضية عند تغطية البنى المكشوفة، حيث يكون العلاج على مرحلة واحدة، مع تقليل فترة الاستشفاء. Background: The defects in the leg is one of the most important challenges facing reconstructive surgeons because of the lack of soft tissue covering the front surface of the leg and the lack of blood perfusion in the lower third of the leg. The muscle and fasciocutaneous flaps are one of the most important reconstruction options as there have been no local studies about this method so far. Objective: Evaluation of methods of reconstruction the defects of the soft tissues of the leg using the muscle flaps and fasciocutaneous flaps and comparing them with the international studies. Methods: The study included 25 patients undergoing transposition of the gastrocnemius and / or soleus flaps, sural flaps for treating soft tissues in the leg, from 2015 to 2017 in both Al-Asaad and Tishreen University hospitals in Lattakia , gathering information on the etiology the lesion, the time of reconstruction, the flap used to cover the lesion, and the function of the gastrocnemius-soleus unit, and the following Sensory disorders. Results: 25 patients were operated, the ages varying between 13 and 55 years (mean age 42); 23 were male and 2 female. The main initial injury was war injuries(60%). The flaps used ware the soleus in 6 cases (24%), gastrocnemious in 5 cases(20%) and sural in 13 cases(52%). There were complete vitality in 19 cases, partial vitality in 5 cases and necrosis in 1 case only. Conclusion: the treatment of the defects in the leg with local flaps (gastrocnemius, soleus and sural) enables obtaining satisfactory results in covering of exposed structures. It offers the advantage of providing a treatment in only one surgical procedure, and reduced hospital stay.